ЁШЛАРДА ҒОЯВИЙ ИММУНИТЕНТНИ ШАКЛЛАНТИРИШ – УЧИНЧИ РЕНЕССАНС ДАВРИНИНГ АСОСИЙ ПОЙДЕВОРИДИР - Қодиров, Қ.А. (SCIENCE and SOCIETY, 2022)
The article shows the need to increase the role and responsibility of class leaders, tutors, parents’ council, public council, teacher-apprentice system, and the organization of the Youth Union, which work closely with young people in the formation of ideological immunity in young people. Recommendations for systematic implementation of continuous monitoring and cooperation are also given. Ideological education of today’s students, future specialists based on the requirements of the new era of Uzbekistan’s development, preparing them for independent professional and spiritual life depends on the activities of teachers, mentors and coaches at all levels of educational institutions.